Anti-Tuberculosis natural products: synthesis and biological evaluation of pyridoacridine alkaloids related to ascididemin - Appleton, D.R.; Pearce, A.N.; Copp, B.R. (Elsevier, 2010)
There is an urgent need for novel therapeutics possessing new modes of action to treat tuberculosis (TB) infections. In this study we report on the synthesis and biological evaluation of a series of pyrido[2,3,4-kI] acridin-6-one alkaloids related to the anti-TB (MIC 0.35 mu M) but cytotoxic (IC(50) <0.14 mu M) marine natural product ascididemin (1). The most interesting compounds identified were 21 and 24, which were found to inhibit the growth of Mycobacterium tuberculosis (Mtb) H(37)Rv with MIC 2.0 mu M, but with negligible cytotoxicity towards Vero and P388 cells (IC(50)>25 mu M). Another analogue (10) was evaluated against a range of singly-drug-resistant strains of Mtb and was found to exhibit no cross-resistance. These results suggest that the pyrido[2,3,4-kI]acridin-6-one skeleton may provide a useful scaffold for future studies directed towards possible anti-TB drugs. (C) 2010 Elsevier Ltd. All rights reserved.